GENETIC PROGRAMMING METHOD FOR CONTROL SYSTEMS IDENTIFICATION - Askhat I. Diveyev; Elena A. Sofronova (Вестник Донского государственного технического университета, 2018)
A problem of structural-parametric control systems identification is considered. The method of genetic programming with the network operator is used. Network operator properties, rules of its creation and application are described. The basic solution approach is used for the genetic algorithm construction. It permits to apply genetic operations to the basic solution variations. The basic solution is set by a developer on the ground of his experience of concrete problem research. The selection of the basis solution influences on effectiveness of genetic algorithm. The results of computational experiment of the problem of identification solution are presented.